THE IMPLEMENTATION OF TERRORISM PREVENTION POLICY: THE CHALLENGES OF COUNTER-RADICALIZATION PROGRAM IN EAST JAVA - Hikam, Reza Maulana (Jurnal Kebijakan Pemerintahan, 2023)
Abstract This study examines the implementation of terrorism prevention policy through a counter-radicalization program carried out by the Coordination Forum for the Prevention of Terrorism of East Java (FKPT East Java). The theoretical framework used is the theory of implementation of public policy with street-level bureaucracy approach fronted by Michael Lipsky to see how lower-level bureaucracy such as FKPT East Java implement policies on preventing terrorism in regional case studies, and Community Engagement Program (CEP) to see how FKPT East Java build networks and collaborate with various stakeholders in East Java to implement policies agreed upon at the National Meetings (National Working Meeting/Rakernas). The research method used is qualitative. The data collection techniques were done through in-depth interviews with several FKPT East Java board members. As well as observations of the implementation of counter-radicalization programs in East Java. Discourse Analysis is used as a data analysis technique to see whether the discourse in the regulations conforms with the interpretation of each of the FKPT East Java board members that have been interviewed. This research will produce an assessment to see whether the interpretation of the interview result conforms with the implementation in the field. The findings of this study indicate that in implementing terrorism prevention policies, FKPT East Java still depends on BNPT despite the efforts to involve FKPT East Java in policy formulation, however, FKPT East Java has considerable discretion in determining cooperation networks in implementing terrorism prevention policies when directly involved on the ground. Keywords: Terrorism Prevention Policy, Counter-Radicalization Program, FKPT East Java